Structural health monitoring of the Santa Casa da Misericórdia Church in Aveiro - Lima, H. F. (2012)
This paper presents a reduced visual impact structural health monitoring system, based on fibre Bragg gratings. This sensing network was developed for the church of Santa Casa da Misericordia of Aveiro and comprises 19 displacement sensors and 5 temperature sensors. All the sensors were custom made, according to the monitoring points’ characteristics. The results obtained over the first year of monitoring are presented